APPLICATION OF PSYCHOSOCIAL THEORIES IN TEAM DYNAMICS AND STRATEGIES FOR PEOPLE MANAGEMENT (CIPEEX, 2025)
This study explores the application of psychosocial theories in the organizational context, aiming to improve teamwork dynamics and organizational cohesion, considering the diversity of profiles and individual needs of employees. The theories addressed include self-efficacy, social identity, and social comparison, which help understand interpersonal interactions and their impacts on organizational behavior. The research adopts a qualitative and descriptive approach, with a bibliographic survey as the initial stage, using SciELO sources. The theoretical analysis reveals how the application of these theories can promote an inclusive organizational culture, stimulating satisfaction, engagement, and well-being of employees, in addition to contributing to the effectiveness of diverse teams. The study concludes that the integration of psychosocial theories can facilitate the creation of more collaborative and adaptable work environments, essential for long-term organizational success.
Keywords: Psychosocial Theories; Social Identity; Social Comparison; People Management.